2012
DOI: 10.1159/000343260
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Growth Restriction and the Innate Immune System in Preterm Infants of ≤32 Weeks Gestation

Abstract: Objective: Intrauterine growth restriction (IUGR) is a well-known cause of adverse neonatal outcomes. As it may have an impact on innate immune responses, we aimed to investigate several parameters of the innate immune response in preterm infants of ≤32 weeks gestation who were small for gestational age (SGA). Methods: We compared clinical data of SGA (n = 20) and appropriate for gestational age (AGA; n = 124) newborns with a gestational age of ≤32 weeks. We investigated full blood counts at birth and on days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 47 publications
3
35
0
4
Order By: Relevance
“…However, no substantial effect was detectable in preterm neonates in our study (data not shown). Severe growth restrictions may also affect innate immune responsiveness in a subset of preterm neonates beyond the attenuation already resulting from prematurity [30]. …”
Section: Discussionmentioning
confidence: 99%
“…However, no substantial effect was detectable in preterm neonates in our study (data not shown). Severe growth restrictions may also affect innate immune responsiveness in a subset of preterm neonates beyond the attenuation already resulting from prematurity [30]. …”
Section: Discussionmentioning
confidence: 99%
“… b Premature infants who are small for gestational age may have leukocyte concentrations that are up to 50% lower than those who are appropriate for gestational age …”
Section: Methodsmentioning
confidence: 99%
“…Both observations may indicate that intrauterine growth restriction (IUGR) finally results in exhaustion of erythropoietic activity. If counted under the microscope, NRBC count tended to be higher in SGA infants compared to AGA [22]. This may indicate a compromise not only in erythropoiesis but also in megakaryopoiesis and granulocytopoiesis of VLBW infants with IUGR.…”
Section: Discussionmentioning
confidence: 94%